2021
DOI: 10.3393/ac.2020.09.14
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis and Recurrence Pattern of Right- and Left-Sided Colon Cancer in Stage II, Stage III, and Liver Metastasis After Curative Resection

Abstract: The prognosis and recurrence pattern of right-and left-sided colon cancer in Stage II, Stage III, and liver metastasis after curative resection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
0
29
0
2
Order By: Relevance
“…The findings of this research are consistent with the previous traditional TNM staging system, which indicate that the prognosis of tumor patients is closely related to primary tumor site, regional lymph node involvement, and distant metastases ( Hari et al, 2013 ). The site of the tumor distant metastasis also matters a lot, compared to those without tumor metastasis, patients with bone metastasis, brain metastasis, lung metastasis, and liver metastasis were at higher risk of death ( Chang et al, 2017 ; Wang et al, 2020 ; Nakamura et al, 2021 ). Additionally, our study showed that different tumor sites of colon cancer had significantly different prognoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this research are consistent with the previous traditional TNM staging system, which indicate that the prognosis of tumor patients is closely related to primary tumor site, regional lymph node involvement, and distant metastases ( Hari et al, 2013 ). The site of the tumor distant metastasis also matters a lot, compared to those without tumor metastasis, patients with bone metastasis, brain metastasis, lung metastasis, and liver metastasis were at higher risk of death ( Chang et al, 2017 ; Wang et al, 2020 ; Nakamura et al, 2021 ). Additionally, our study showed that different tumor sites of colon cancer had significantly different prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the factors that affect the prognosis of CC mainly come from the tumor aspect, including the size of the tumor, the location of the tumor, and the depth of tumor infiltration ( Feng et al, 2021 ; Huang et al, 2021 ; Wang et al, 2021 ). Of course, distant metastasis also contributed to the reduction in the survival of CC patients ( Chang et al, 2017 ; Nakamura et al, 2021 ). Clinically, CC can easily metastasize to other parts of the body, the most frequently metastatic organs were lung and liver, followed by bone and brain ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results, however, have been variable. Some studies have shown that LVI is a significant prognostic factor for either RFS or OS [ 11 , 24 ]. In contrast, other studies have reported no effect of LVI on RFS or OS [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-risk prognostic features such as preoperative obstruction, perineural invasion (PNI), lymphovascular invasion (LVI), <12 lymph nodes retrieved, poor differentiation, and resection margin involvement have been used when deciding whether adjuvant chemotherapy is indicated for patients with pT3N0 colorectal cancer [ 2 , 3 ]. Among the risk factors, LVI and PNI are well known and common pathologic high-risk features for oncologic outcome [ 10 , 11 , 12 ]. In particular, LVI has been considered a possible predictor of occult lymph node metastasis [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, colon cancer is mainly treated with surgery combined with chemotherapy (1,2). Great progresses have been made in the early discovery and treatment of colon cancer; as a result, its morbidity and mortality rates decrease by 30-50% among the relapsed or metastatic cases in 5 years of treatment (3). Oxaliplatin is a kind of third-generation platinum-based anticancer drug and a diaminocyclohexane (DACH) platinum, which is now adopted for treating diverse cancers (4,5).…”
Section: Introductionmentioning
confidence: 99%